Frankenstein doesn't start food fights - Dadey, Debbie; Jones, Marcia Thornton; Gurney, John Steven, 1962- (New York : Scholastic, 2003)
The Bailey School kids suspect that the man selling cookies in the school cafeteria is Frankenstein's monster.
007-010.
550
Accelerated Reader AR
Keywords: Frankenstein (Fictitious character) -- Juvenile fiction; Monsters -- Juvenile fiction; Schools -- Juvenile fiction